Violence in Bits and Pieces – Cinema and Social Power Structures (KULT_online, 2012)
Contributing to the many studies on media violence, David Hansen-Miller's Civilized Violence offers an interesting perspective by means of discussing the functions of violence representation in films. David Hansen-Miller highlights the entanglements between cinema and society, and brings together theories of subjectivation and biopolitics with gender studies and film theories. The author conducts a close reading of several films, and, in result, emphasizes that cinema as a cultural product has played an important role in the discourse of subjection and subjectivation through violence since its beginnings. Concluding with a chapter on contemporary movies, Hansen-Miller underlines his assumption that cinema has the ability to narrate and interpret social forces that generally have become too opaque to be detected easily in social structures.